Characteristics of Frailty in Haemodialysis Patients. (21st April 2022) - Hendra, Heidy; Sridharan, Sivakumar; Farrington, Ken; Davenport, Andrew
Background: Both frailty and cachexia increase mortality in haemodialysis (HD) patients. The clinical frailty score (CFS) is a seven-point scale and less complex than other cachexia and frailty assessments. We wished to determine the characteristics of frail HD patients using the CFS.Methods: Single centre cross-sectional study of HD patients completing physical activity questionnaires with bioimpedance measurements of body composition and hand grip strength (HGS).Results: We studied 172 HD patients. The CFS classified 54 (31.4%) as frail, who were older (70.4±12.2 vs 56.2 ± 16.1 years, p < 0.001), greater modified Charlson co-morbidity (3 (2–3) versus 1.5 (0–3), p < 0.001), and body fat (33 (25.4–40.2) versus 26.2 (15.8–34) %, p < 0.01), but lower total energy expenditure (1720 (1574–1818) versus 1870 (1670–2194) kcal/day, p < 0.01), lean muscle mass index (9.1 (7.7–10.1) versus 9.9 (8.9–10.8) kg/m2), and HGS (15.3 (10.3–21.9) versus 23.6 (16.7–34.4) kg), both p < 0.001. On multivariable logistic analysis, frailty was independently associated with lower active energy expenditure (odds ratio (OR) 0.98, 95% confidence limits (CL) 0.98–0.99, p = 0.001), diabetes (OR 5.09, CL 1.06–16.66) and HGS (OR 0.92, CL 0.86–0.98).Discussion: Frail HD patients reported less active energy expenditure, associated with reduced muscle mass and strength. Frail patients were more likely to have greater co-morbidity, particularly diabetes. Whether physical activity programmes can improve frailty remains to be determined.